[PP.03.10] ASSOCIATION BETWEEN DISEASE SEVERITY AND HYPERTENSION IN PATIENTS WITH OSTEOARTHRITIS. (September 2016) - Triantafyllou, G.; Anyfanti, P.; Panagopoulos, P.; Koletsos, N.; Triantafyllou, A.; Pyrpasopoulou, A.; Chatzimichailidou, S.; Kiourka, Z.; Aslanidis, S.; Douma, S.
Abstract : Objective: Recent epidemiological data suggest that patients with osteoarthritis may exhibit higher rates of cardiovascular mortality and morbidity, potentially through increased prevalence of concomitant cardiovascular risk factors or pathways mediated by chronic low-grade inflammation. In this study, we aimed at investigating whether osteoarthritis severity is associated with hypertension, in a population of osteoarthritis patients seeking medical care in a tertiary rheumatology outpatient clinic. Design and method: Consecutive patients with hip and/or knee osteoarthritis attending the Rheumatology Outpatient Clinic of our Department were recruited. Severity of the disease was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), one of the most widely utilized self-report measures of lower extremity symptoms and function. Total score, function, stiffness and pain subscale scores were calculated and analyzed in respect to clinical and epidemiological data obtained from the medical history and clinical examination of the patients. Results: A total of 91 patients, 86 females and 5 males, with a mean age of 61.8 ± 10.3 years, and median disease duration of 4 (2–9) years, were included in the study. 46.7% of the patients had hypertension, while mean systolic/diastolic blood pressure (SBP/DBP) was 135.7 ± 17.4/81.5 ± 9.7 mmHg. Mean WOMAC total score was 36.0 ± 17.6; mean pain, function and median stiffness subscale scores were 7.5 ± 4.2, 25.8 ± 13.1 and 3.0 (1–4), respectively. WOMAC total index was higher among patients with hypertension compared to those with normal blood pressure levels, but did not reach statistical significance (39.3 ± 16.9 vs 32.8 ± 18.0, p = ns). Likewise, pain, stiffness and function indices were comparable between hypertensive and normotensive patients. Neither WOMAC total score nor WOMAC pain and function scores significantly correlated with SBP/DBP. However, a significant association was observed with WOMAC stiffness index and DBP (rho = 0.321, p = 0.030). Conclusions: Although some evidence suggests that osteoarthritis patients may be at increased risk for hard cardiovascular outcomes, severity of osteoarthritis was not associated with hypertension in our population. Further studies are needed to clarify whether a straight-forward association exists between osteoarthritis and cardiovascular diseases.